Anti-Tumor TCF1+ CD8 T Cells are Functionally Diverse and Evolve During Tumorigenesis and Progression. (28th October 2020) - Schenkel, Jason; Herbst, Rebecca; Canner, David; Li, Amy; Hillman, Michelle; Smith, Olivia; Rozenblatt-Rosen, Orit; Regev, Aviv; Jacks, Tyler
Abstract: CD8+ T cells drive protective responses against infection and cancer. In the context of chronic antigen stimulation, CD8+ T cells become progressively dysfunctional, losing the ability to proliferate, secrete cytokines, and kill target cells. While dysfunctional CD8 T cells have been characterized in infection, studies examining longitudinal responses in tumors have been limited. Here, in an autochthonous model of lung adenocarcinoma using high dimensional flow cytometry and single cell RNA sequencing, we demonstrate that tumor specific CD8 T cell heterogeneity is dynamic, revealing multiple dysfunctional-like CD8 T cell populations. Among these states, we identify TCF-1+ CD8 T cells, a population previously associated with superior functionality. Temporal analysis revealed heterogeneity within the TCF-1+ CD8+ T cell compartment - SlamF6+ CD8 T cells were predominant in early stage disease, while SlamF6- CD8 T cells appeared later and were the majority during progression. Functionally, the SlamF6+ population was proliferative and expressed more inhibitory receptors than SlamF6- cells. However, SlamF6+ CD8 T cells gradually lost the ability to divide and secrete cytokines over the course of tumorigenesis, demonstrating that they become dysfunctional over time. Collectively, our results provide new insights into longitudinal response of TCF-1+ T cells over the course of tumorigenesis and have therapeutic implications for modulating the anti-tumor T cell response.